AGE-DEPENDENT VARIATIONS IN THE RESPONSE TO TOPICAL LUBRICATION IN PATIENTS WITH DRY EYE DISEASE - MIRANI , AH; MEMON , S; NAEEM , M; SIDDIQI , A; ASHRAF , R; AQIL, B; LATIF, MMA; KHATOON, F (Biological and Clinical Sciences Research Journal, 2024)
Dry Eye Disease (DED) is a prevalent ophthalmological condition characterized by tear film instability and ocular surface damage, leading to eye discomfort, visual disturbances, and inflammation. Objective: To analyze the age-dependent response to topical lubrication in patients with DED over a period from May 2023 to October 2023 in a cohort of 90 patients. Methods: This prospective observational study was conducted at Ghulam Muhammad Mahar Medical College Sukkar during May 2023 till October 2023. The study enrolled 90 patients with clinically diagnosed DED. Patients were stratified into three age groups: 18–35 years, 36–55 years, and 56+ years. Each patient received topical lubrication treatment, and data on symptom severity, tear break-up time (TBUT), ocular surface staining, and Schirmer's test results were recorded at baseline, 1 month, 3 months, and 6 months. Results: The study revealed that older patients (56+ years) had a slower and less robust response to topical lubrication compared to younger groups. Improvements in TBUT, Schirmer’s test, and symptom relief were more significant in the 18–35 age group, indicating better ocular surface recovery. Conclusion: The response to topical lubrication in DED varies significantly with age, with younger patients showing better and faster improvement in clinical outcomes. Personalized age-specific treatment strategies may be essential for optimizing DED management.